CHARACTERIZATION OF TELUK SEPANG COASTAL LOCAL SEISMIC RESPONSE USING MICROTREMOR HVSR ANALYSIS - Gita Panny Nababan; Agung Wijaya; Basdiki Hasugian; Marven Saputra; Budi Harlianto; Suhendra Suhendra (Engineering Faculty Universitas Lampung, 2026)
The coastal area of Teluk Sepang, Bengkulu City, Sumatra, Indonesia, is dominated by young alluvial and marine sediments that are highly susceptible to seismic wave amplification due to tectonic activity along the Indo-Australian–Eurasian subduction zone. This research aims to characterize local seismic response and map soil dynamic properties using microtremor data analyzed with the Horizontal to Vertical Spectral Ratio (HVSR) method. Microtremor measurements were conducted at several observation points with a sampling interval of 5 ms capable of and a recording duration of 30 minutes at each site. The recorded data were processed using the HVSR method through windowing, Fourier transform, and spectral ratio analysis to obtain the dominant frequency (f₀), amplification factor (A₀), and seismic vulnerability index (Kg). The results show that low f₀ values are associated with thick soft sediments, while high A₀ values indicate stronger amplification potential. High Kg values are identified in areas where low f₀ coincides with high A₀, reflecting greater seismic vulnerability. These results reveal significant spatial variability in local seismic response across the study area. This study provides new site-specific insights into seismic vulnerability in coastal environments and contributes to improving seismic hazard assessment and coastal development planning in Bengkulu City.